Zur Inhaltsstruktur von Rechtsnormen: Modalitäten und Normtypen - Lötscher, Andreas (ZERL - Zeitschrift für Europäische Rechtslinguistik, 2011)
Legal Norms as Texts – An attempt to combine legal theory and linguistics: While legal theorists may well be aware of the fact that the law is essentially language, this aspect is only rarely taken into consideration in the concrete analysis of legal norms and their structure. It is generally the case that concrete linguistic forms are disregarded, or indeed, that individual phrases or sentences are taken to be as a formal, absolute whole. In addition, important linguistic characteristics are often scarcely examined – for, example, fundamental differences such as those between the sentence and the text, grammar and utterance, or expression and content. This article is an attempt to address the issue of legal norms as written texts sui generis, that is, as linguistic objects, and to examine them from a textual linguistic perspective. Moreover, legal norms will be thoroughly assessed within the context of legal theory and its academic insights, and the fundamental characteristics of legal norms will thus be clarified from both the legal and linguistic perspectives. Aspects include the internal structure of legal norms, a typology of legal norms, the meaning of individual norms, and the relationship between the internal structure and the external form or the question of who is being addressed.